Channel heads in mountain catchments subject to human impact – The Skrzyczne range in Southern Poland - Wrońska-Wałach, Dominika; Żelazny, Mirosław; Małek, Stanisław; Krakowian, Katarzyna; Dąbek, Natalia (Geomorphology (Amsterdam, Netherlands), 2018)
Channel heads in mountain catchments are increasingly influenced by human activity. The disturbance of mountain headwater areas in moderate latitudes by the clearing of trees and the associated logging, road building and hydrotechnical constructions contribute to changes in the water cycle and consequently may induce a change in channel head development. Here we examine channel heads in the Beskid Śląski Mts., one of the areas most affected by ecological disaster in the Polish Flysch Carpathians. An ecological disaster associated with the decline of spruce trees in the 1980s and 1990s caused a substantial decrease (of about 50%) in the land area occupied by spruce forest in the Beskid Śląski Mts. As a result, headwater areas were subject to multidirectional changes in the environment. The purpose of this paper is to determine the detailed characteristics of channel heads currently developing in the analyzed headwater areas, as well as to identify independent factors that affect the evolution of channel heads. Geomorphological mapping was conducted in 2012 in the vicinity of springs in the study area. One-way ANOVA was used to determine the significance of differences between mean values calculated for groups identified based on: i) geomorphologic processes (hollows with rock veneer - h, spring niches - sn, gullies - g), ii) location vs. transformation of channel heads (forested areas vs., deforested areas with road constructions). Principal component analysis (PCA) was used to determine the structure and general patterns associated with relationships between the parameters of a channel head and its contribution area, as well as to identify and interpret new (orthogonal) spaces defined using distinct factors. As far as we know, this kind of approach has been never applied before. A total of 80 channel heads surrounding 104 springs were surveyed close to the main ridge in the study area. A total of 14 morphometric parameters were taken into account in this study. The analyzed landforms substantially differ from one another in relation to groups identified based on morphogenetic processes and with respect to time. Multidimensional PCA analysis made it possible to identify three independent, main factors that together explain 81.9% of total variance. It was concluded that the major factor today is human impact, which alters natural geomorphic processes. The second factor is connected with the type of water circulation. The third factor, which explains only 12.7% of variance, is a geologic factor defined in terms of structural integrity. Although our results are region-specific, at least some general conclusions may be drawn. The main general conclusion is that multidimensional human impact may lead to an increase in the fragmentation of mountain headwater areas over the long term. •Morphometry of channel heads: initial hollows and gullies, spring niches and zero-order catchments are analyzed.•ANOVA and PCA analysis was used to identify independent factors determining the development of initial hollows.•Multidimensional PCA indicates that there are three factors that do determine the evolution of initial hollow landforms.•It was concluded that over the long term, human impact may lead to an increase in the fragmentation of headwater areas.